2018
DOI: 10.3390/ma12010115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agriculture and Construction Wastes on the Properties of Magnesium Oxychloride Cement Mortar with Tourmaline Powder

Abstract: This research attempted to develop an environmentally-friendly functional building mortar by the combined use of agriculture wastes (agro-wastes) and construction wastes in magnesium oxychloride cement (MOC). The agro-wastes referred to corn stalk (CS) and saw dust (SD), which were used to improve the flexural properties of host cementitious material, whilst the construction wastes referred to recycled clay brick powder (CBP), which was employed to enhance compressive strength and water resistance. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…All of the efforts to counteract the disadvantage of poor water resistance imply the use of various additives in the mixture, and despite the effectiveness of additives in improving the properties of MOC, the cost of the end-materials is unfavorably increased [ 55 ]. Thus, in order to develop a more sustainable and cost-effective building material, MOC cement must be mixed with other low-cost materials, in general waste from different sources such as waste-expanded polypropylene-based aggregate [ 56 ], waste gypsum [ 57 ], agricultural and construction waste [ 55 ], granite waste [ 46 ] or various wood waste [ 58 ] such as waste from the construction and demolition [ 59 ], especially waste from concrete timber formwork [ 7 ].…”
Section: Background Of Magnesium Oxychloride Cement (Moc)mentioning
confidence: 99%
“…All of the efforts to counteract the disadvantage of poor water resistance imply the use of various additives in the mixture, and despite the effectiveness of additives in improving the properties of MOC, the cost of the end-materials is unfavorably increased [ 55 ]. Thus, in order to develop a more sustainable and cost-effective building material, MOC cement must be mixed with other low-cost materials, in general waste from different sources such as waste-expanded polypropylene-based aggregate [ 56 ], waste gypsum [ 57 ], agricultural and construction waste [ 55 ], granite waste [ 46 ] or various wood waste [ 58 ] such as waste from the construction and demolition [ 59 ], especially waste from concrete timber formwork [ 7 ].…”
Section: Background Of Magnesium Oxychloride Cement (Moc)mentioning
confidence: 99%
“…Various fillers/modifiers have been utilized to improve MOC composites. In a recent study, recycled clay brick powder (CBP) was investigated as an alternative low-cost waste pozzolanic material for MOC mortar reinforced with agricultural residues, namely corn stalk and wood sawdust (Chen et al 2019). Due to the higher water absorption capacity of the CBP, the fluidity and workability of freshly blended agro-waste MOC mortars consistently decreased with increasing CBP content up to a maximum CBP content of 15%.…”
Section: Effect Of Modifiers/fillers Mocmentioning
confidence: 99%
“…For example, it was reported that marine clay can be utilized with high added value as a supplementary binding material in manufacturing sustainable concrete products [22,23]. Recycled fine aggregates and recycled glass powder can be co-used in concrete production, which reduces the total carbon dioxide emission by about 19% [24,25]. Incinerated sewage sludge ash sourced from the incineration of sewage sludge could be used with lime to produce building materials that are eco-friendly [26].…”
Section: Introductionmentioning
confidence: 99%